Increased risk of severe vaso‐occlusive episodes after initial acute chest syndrome in children with sickle cell anemia less than 4 years old: Sleep and asthma cohort. Issue 5 (30th March 2015) - Vance, Leah D.; Rodeghier, Mark; Cohen, Robyn T.; Rosen, Carol L.; Kirkham, Fenella J.; Strunk, Robert C.; DeBaun, Michael R.
<x xml:space="preserve">Abstract</x> Previous studies have shown that the highest incidence of acute chest syndrome (ACS) in sickle cell disease occurs in children <4 years old, and a history of ACS at this age is a risk factor for future ACS episodes. However, the interval associated with the highest risk of subsequent ACS or severe pain is not known. Through this mixed retrospective‐prospective observational study, the Sleep and Asthma Cohort, we sought to determine the interval after an initial ACS episode during which the majority of children <4 years old are rehospitalized for ACS or severe pain. The cumulative prevalence of rehospitalization for ACS or severe pain within 6 months, 1 years, and 2 years was calculated for children with an initial ACS episode <4 years old and compared to children with an initial ACS episode ≥4 years old. A total of 44.8% and 55.2% of participants had an initial ACS episode <4 years and ≥4 years old (Range: 4–17.7 years), respectively. At 1 year following the initial ACS episode, children <4 years old had a significantly higher cumulative prevalence of rehospitalizations for ACS or pain as compared to children ≥4 years of age, 62.5 and 39.1%, respectively (P = 0.009). After initial ACS episodes, the majority of children <4 years old will be rehospitalized for ACS or severe pain within one year, suggesting the need for a therapeutic intervention for this high‐risk group. Am. J. Hematol. 90:371–375, 2015. © 2015 Wiley Periodicals, Inc.